Experimental Filmmaking : Break the Machine - Ramey, Kathryn (Focal Press, 2016)
Experimental Filmmaking emerges out of a deep and abiding love of celluloid and artisanal media practices and a personal exploration of the field of avant-garde and experimental film, animation and video produced since the beginnings of cinema. Although there have been many critical and historical books on the subject, with the exception of zines and hand-published volumes, there has never been a comprehensive instructional manual on experimental processes. This book will introduce film students and professional filmmakers alike to various methods of experimental animation, film and video production that involve material interventions into the normative process of the medium while offering brief introductions to artists and their works.